Correlation Of Linear Measurements Of Spleen With Splenic Volume in Computed Tomography - Suwal , S; Subedi , K; Gurung , G (Journal of Institute of Medicine Nepal, 2018)
Introduction: The purpose of this study was to assess the normal linear measurements of spleen in Nepalese adults by Computed Tomography (CT) and their correlation with splenic volume. Methods: This was a prospective cross sectional observational study done in 264 peoples undergoing abdominal CT examination for various clinical indications not pertaining to spleen, in Department of Radiology & Imaging, Tribhuvan University Teaching Hospital (TUTH). Four linear measurements of spleen were obtained in axial plane. Craniocaudal length of the spleen was also obtained. The volume was obtained by adding cross-sectional area of spleen from 10 mm contiguous axial images and multiplying them with the slice thickness. The relationships between various linear measurements of spleen with spleenic volume were derived. Results: The mean length of spleen along long axis was 9.3 +/- 1.3 cm, and the mean length along the craniocaudal axis was 7.6 +/- 1.5 cm. The mean width, maximum thickness, and thickness at hilum of the spleen were 9.3 +/- 1.7 cm, 5.1 +/- 1.2 and 3.2 +/- 0.6 cm respectively. The mean splenic volume was 151.20 cm3 ± 59.62 cm3. Significant positive correlations were noted between linear measurements and volume, the strongest being the width followed by the craniocaudal length. Conclusion: Linear measurements of the spleen in CT show strong correlation with volume and hence can replace the splenic volume measurements while defining splenomegaly